(untitled) (Journal of Science and Technology, 2016)
This article discusses the complementary role of distance education in post-secondary/tertiary education. Effective management of library/information services in support of distance education ensures a higher level of success in the programme. The traditional methods of library and information provision are discussed together with proposals for a mixture of the old with ICT services. Strategic policies and plans should be evolved to co-ordinate library/information services for distance education from a centralised institution.